(untitled) (Ciudades, 2017)
Summary of the PhD Resumen de la Tesis Doctoral "Shopping (&) Center: sobre o consumo, a cidade e os centros comerciais em Portugal e na Europa‟‟, by Miguel Farinha Dos Santos Da Silva Graça un the University Institute of Urban Research of the University of Valladolid on May 24th, 2011. Directors: Professor Emeritus Nuno Portas and PhD Professor María Castrillo Romón. Board: PhD Professor Juan Luis de las Rivas Sanz, PhD Professor Helena Villarejo Galende, PhD Professor Teresa Barata Salgueiro, Professor Corinna Morandi and PhD Professor Ramón López de Lucio.